2015
DOI: 10.1111/ejh.12571
|View full text |Cite
|
Sign up to set email alerts
|

A cost‐effectiveness analysis of real‐world treatment for elderly patients with multiple myeloma using a full disease model

Abstract: Our patient-level model enabled to study the effects and costs of entire treatment sequences and to compare real-world treatment patterns over time. Increased utilisation of novel agents improved survival and increased costs for real-world patients with MM in the Netherlands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 38 publications
2
35
0
Order By: Relevance
“…Additionally, bortezomib‐based interventions were considered cost‐effective in most included studies, with incremental ratios ranging from dominant to $94 047/LY and $141 070/QALY. Finally, the only economic evaluation based on real‐world data showed that the thalidomide, lenalidomide, bortezomib sequence would be the most cost‐effective for elderly patients with MM …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, bortezomib‐based interventions were considered cost‐effective in most included studies, with incremental ratios ranging from dominant to $94 047/LY and $141 070/QALY. Finally, the only economic evaluation based on real‐world data showed that the thalidomide, lenalidomide, bortezomib sequence would be the most cost‐effective for elderly patients with MM …”
Section: Resultsmentioning
confidence: 99%
“…After reviewing the titles and abstracts, 16 articles were selected for full-text examination. Of these, eight economic studies [14][15][16][17][18][19][20][21] fully met the eligibility criteria and were included in this systematic review. Excluded studies and reasons for their exclusion are detailed in Appendix S2.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 provides an overview of the mission and goals of the registries in which we are involved. All registries ensure transparency to the public through presentations and publications [7][8][9][10][11][12][13][14]. However, only the melanoma registry (Dutch Melanoma Treatment Registry [DMTR]) fortnightly provides clinicians with online benchmarked feedback regarding a predefined set of quality indicators developed by the professional organization.…”
Section: Mission and Goals ("The Why")mentioning
confidence: 99%
“…An intervention-based registry addresses research questions regarding appropriate use, effectiveness, cost-effectiveness, and safety. Disease-based registries provide additional information and facilitate studying the full disease course including (sequential) treatment pathways [11]. Furthermore, such a registry provides information on the number of untreated patients and whether these patients would have been eligible for treatment.…”
Section: Type and Content ("The What")mentioning
confidence: 99%